The Politicizing of Judicial Independence: Cases and Controversy in Indonesian Constitutional Court’s - Idul Rishan (Fakultas Hukum Universitas Gadjah Mada, 2024)
The Constitutional Court has been the target of several political attacks over the past three years, each with its tactics and goals. The politicization of the court by the government poses the greatest danger to its independence. This study combines qualitative analysis with socio-legal study methodology. According to this study, the court gets politicized in two ways. The first type is extrajudicial, which indicates that political actors acting outside the court system constitute. The second type is intra-judicial, which involves the major actors in the legal system. In this case, the major actors are the judges of the Constitutional Court. This study also elucidates the way certain components with a legal component and others with a socio-political component resulted in the politicization of the independence of the constitutional court.